2017
DOI: 10.5897/ijbc2016.1061
|View full text |Cite
|
Sign up to set email alerts
|

Hydroclimatic variability and flood risk on Naglanou and Akissa forests areas in Mono River Delta (West Africa)

Abstract: ). Return periods correspond to 2, 10, 20 and 50 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Diallo et al [19] analyzed the inter-annual variability using several climate models over Sahel region and concluded that the models can reproduce rainfall variability with correlation exceeding 0.6 compare to observations. Amoussou et al [20] reviewed hydroclimatic variability and flood risk in two small forests located in the Mono River Basin (MRB). Lawin et al [21,22] studied climate extreme trends of temperature and rainfall using a single model of Coordinated Regional Downscaling Experiment (CORDEX) and later with REgional MOdel (REMO) and consedering a few number of stations in the MRB.…”
Section: Introductionmentioning
confidence: 99%
“…Diallo et al [19] analyzed the inter-annual variability using several climate models over Sahel region and concluded that the models can reproduce rainfall variability with correlation exceeding 0.6 compare to observations. Amoussou et al [20] reviewed hydroclimatic variability and flood risk in two small forests located in the Mono River Basin (MRB). Lawin et al [21,22] studied climate extreme trends of temperature and rainfall using a single model of Coordinated Regional Downscaling Experiment (CORDEX) and later with REgional MOdel (REMO) and consedering a few number of stations in the MRB.…”
Section: Introductionmentioning
confidence: 99%
“…LULC spatial trend direction and location are approximately situated in the locations of the main cities of the basin, therefore, LULC spatial trend can be explained by population activities and growth as mentioned by Koglo et al (2018) in the south district of MRB. Because of its fine resolution, the Nangbéto dam area and some protected forests such as Malafacassa (Amoussou et al, 2017;Atsri et al, 2018) are well delimited. The excellent reclassification of these land cover is due to low and high albedo factor of water and forest which plays a role during data collection by satellite's sensors.…”
Section: Land Use and Land Cover Scenarios Accuracy And Assessmentmentioning
confidence: 99%
“…Most of these studies compared specific climate parameters to household perceptions in general for determining adaptive strategies, but less attention was given to flooding. In addition, despite many studies were conducted in the Lower Mono River (LMR) catchment for analyzing the climatic and hydrological causes of flood and getting more insight in its causes in the study area [33][34][35][36][37], the information on local communities and stakeholders perceptions on this matter remain limited. [38] noted that local community perception is an important predictor for flood mitigation in the catchment.…”
Section: Introductionmentioning
confidence: 99%